Caring and Resisting in the Territory: Mental Health and Care in Afro-Descendant Rural Communities in Lopez de Micay, Colombia - Garces-Riascos, Milly Yesenia; Bedoya-Durán, Eliana Isabel (Prospectiva. Revista de Trabajo Social e Intervención Social, 2026)
This study aimed to understand the constitutive elements of mental health and the caregiving practices developed by six community mothers, between 30 and 60 years old, residing in the suburb of Chuare, in López de Micay, Colombia. A qualitative methodology was employed, using the Photovoice technique; through reflexive thematic analysis, recurring patterns were identified, enabling the construction of meaningful categories based on the participants’ experiences. The findings reveal that the participants hold a multifaceted understanding of the concept of care and mental health in relation to motherhood, health, and well-being. The study thus demonstrates that care and mental health are shaped by situated and relational practices that are deeply influenced by gender, culture, and territory. In this sense, community mothers emerge as fundamental agents in fostering collective well-being, integrating traditional knowledge, affective bonds, and daily practices that sustain life.